PROBLEMATIKA PEMBAHARUAN BLANKO SERTIPIKAT BAGI PEMEGANG HAK ATAS TANAH - MARIANA MARIANA (PREMISE LAW JURNAL, 2015)
This renewal of certificate blank is mainly intended to obtain an orderly land administration, protection, and legal certainty either for physical or juridical data. The problem raised in the process of this renewal of certificate blank is when about to trasfer right the holder of old certificate blank is required to renew his/her the certificate blank he/she holds. The old certificate blank must be changed with the new one issued by the National Land Board (BPN). This needs time and higher cost because to renew the blank, the land owned by the holder of old certificatye blank must be remeasured to obtain a new measurement certificate, even though, various problems that are not maximally efficient where its application has positive and negative sides in terms of certificate ownership are, in fact, found. If this policy can be applied efficiently well, the legal certainty of the renewal of certificate blank can be well materialized. Therefore, the government in this case shouldpay attention to the problems occured due to the inefficiency found in the process of the renewal of certificate blank. Keywords: Problematics, Renewal of Certificate Blank, Holder of Right to Land